2020
DOI: 10.1186/s13018-020-1555-5
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II blockade had no effect on range of motion after total knee arthroplasty: a retrospective review

Abstract: Background Stiffness and pain from arthrofibrosis following total knee arthroplasty (TKA) is a challenging problem, and investigating methods to prevent or reduce the incidence of postoperative arthrofibrosis is critical. Studies have shown that angiotensin-converting enzyme inhibitors (ACEIs) and angiotensin receptor blockers (ARBs) are efficacious at preventing fibrotic disorders in the lungs, liver, kidneys, and eyes. Our aim was to determine if ACEI or ARB use postoperatively reduces the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Three recent studies have investigated the effect of ACE-Is/ARBs on the incidence of postoperative arthrofibrosis, ROM, and manipulation in total knee arthroplasty. 2 , 18 , 25 None of the three studies demonstrated significant improvement in postoperative ROM, reduction in need for MUA, or decreased revision rate. The most recently published study by Arraut et al evaluated 79 patients undergoing primary total knee arthroplasty who were prescribed losartan at least three months prior to surgery, matched with a control group of patients who were not taking losartan.…”
Section: Discussionmentioning
confidence: 88%
“…Three recent studies have investigated the effect of ACE-Is/ARBs on the incidence of postoperative arthrofibrosis, ROM, and manipulation in total knee arthroplasty. 2 , 18 , 25 None of the three studies demonstrated significant improvement in postoperative ROM, reduction in need for MUA, or decreased revision rate. The most recently published study by Arraut et al evaluated 79 patients undergoing primary total knee arthroplasty who were prescribed losartan at least three months prior to surgery, matched with a control group of patients who were not taking losartan.…”
Section: Discussionmentioning
confidence: 88%
“…The association between the use of ARBs and functional outcomes has been investigated in other human pain conditions including total knee arthroplasty, migraine and chemotherapy-induced neuropathy [16][17][18]. Patients using ARBs did not show any improvement in knee flexion scores after total knee arthroplasty and volunteers with experimental ischaemic pain [4,16]. However, in other pathologies such as migraine, Diener et al [17] demonstrated that telmisartan reduced pain severity compared to placebo.…”
Section: Discussionmentioning
confidence: 99%
“…The association between the use of ARBs and functional outcomes has been investigated in other human pain conditions including total knee arthroplasty, migraine and chemotherapy-induced neuropathy. [1618] Patients using ARBs did not show any improvement in knee flexion scores after total knee arthroplasty and in volunteers with experimental ischemic pain. [4, 16] However, in other pathologies like migraine, Diener et al demonstrated that telmisartan reduced pain severity compared to placebo.…”
Section: Discussionmentioning
confidence: 99%
“…[1618] Patients using ARBs did not show any improvement in knee flexion scores after total knee arthroplasty and in volunteers with experimental ischemic pain. [4, 16] However, in other pathologies like migraine, Diener et al demonstrated that telmisartan reduced pain severity compared to placebo. [17] Interestingly, the use of ACEis and ARBs was associated with some protection of myelinated fiber function in a mixed population of patients with chemotherapy-induced neuropathy.…”
Section: Discussionmentioning
confidence: 99%